Extrascleral Vitreous Prolapse Following Intravitreal Injection. (November 2017) - Haddock, Luis J.; Lyttle, Deanna P.; Rosenfeld, Philip J.
An 82-year-old man presented with right eye discomfort 3 days after an intravitreal aflibercept injection using a 32-gauge needle for treatment of neovascular age-related macular degeneration. His visual acuity was stable however slit lamp examination of the right eye showed prolapsed vitreous extending to the lower eyelid arising from the inferotemporal pars plana scleral injection site. There was no evidence of intraocular inflammation and his fundus examination was stable. The scleroconjunctival defect and prolapsed vitreous were repaired in the operating room. Postoperatively his vision remained stable with no signs of endophthalmitis or retinal detachment.